2017
DOI: 10.4309/jgi.v0i36.3986
|View full text |Cite
|
Sign up to set email alerts
|

Closing a Treatment Gap in Ontario: Pilot of a Tutorial Workbook for Women Gamblers

Abstract: Past research has shown that treatment services for problem gambling are being underutilized in Ontario, especially by women. Our pilot study involves the development of a Tutorial Workbook (TW) designed specifically to address the special issues and treatment needs of women who gamble and develop consequent problems. Investigators tested the effectiveness of the intervention and reviewed comments from women gamblers on the contents and layout of the workbook. The TW study involved 12 modules and required prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This is not surprising given the impulsive nature of problem gambling. Previous studies have found that people with gambling problems have a poor record of commitment to long therapy (Bartel et al, 2020, Rush, Moxam, & Urbanoski, 2002Toneatto, 2016;Wall et al, 2021) and the attrition rate in therapy is high (Wulfert, Blanchard, Freidenberg, & Martell, 2006;Boughton et al, 2017;Wall et al, 2021). For example, in a recent study of brief support by Wall et al (2021) only 23% of the participants completed all 4 modules, and only 10% of the participants completed the gambling log for longer than 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is not surprising given the impulsive nature of problem gambling. Previous studies have found that people with gambling problems have a poor record of commitment to long therapy (Bartel et al, 2020, Rush, Moxam, & Urbanoski, 2002Toneatto, 2016;Wall et al, 2021) and the attrition rate in therapy is high (Wulfert, Blanchard, Freidenberg, & Martell, 2006;Boughton et al, 2017;Wall et al, 2021). For example, in a recent study of brief support by Wall et al (2021) only 23% of the participants completed all 4 modules, and only 10% of the participants completed the gambling log for longer than 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent study of brief support by Wall et al (2021) only 23% of the participants completed all 4 modules, and only 10% of the participants completed the gambling log for longer than 14 days. Similarly, Boughton et al (2017) had a completion rate of 44% (11/25) and only 15% of her clients attended all 12 of her webinar sessions. In addition, in the current study, among the 16 participants who completed the pre-treatment…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A gender-responsive framework for care will acknowledge how women's pathways into gambling and their help-seeking differ from men and within diverse groups of women. Several studies from across disciplines (gambling, addiction, criminal justice) point to the need for gender-responsive treatment that addresses the unique needs and experiences of women (Boughton, 2003;Boughton et al, 2017;Covington & Bloom, 2007;Covington et al, 2008;Wright et al, 2007). Future research must gather knowledge on the needs of women who seek shelter services to better tailor treatment to their unique situations.…”
Section: New Directionsmentioning
confidence: 99%